(untitled) - Katō, Hidetoshi (Honolulu)
Japanese mass communication studies were started to be influenced by the American mass communication studies after the second world war. I. Shimizu published “Social Psychology” (1951). The book was very influential to the early studies of mass communication. He argued the tremendous impact of mass communication on the modern society. That work was the Japanese theory of the mass society. Most japanese researchers of mass communication studies tried to seek the breakthrough of “Shimizu theory”. They warns against the tendency of overemphasizing mass media's effects and saw the active cognitive aspects of audience and personal communication networks as the source of the power of people's resistance against the power of a huge mass communication. These studies have produced the Japanese native perspective of mass communication process. That was a perspective which grasped the mass communication process including total social communication process as the multi-layered structure of conflicts and contradictions.
Keywords: Truyền thông đại chúng,Mass media; Khía cạnh xã hội,Tóm lược,Social aspects,Abstracts; Nhật Bản,Japan